2007
DOI: 10.1371/journal.pgen.0030083
|View full text |Cite
|
Sign up to set email alerts
|

Zip4/Spo22 Is Required for Class I CO Formation but Not for Synapsis Completion in Arabidopsis thaliana

Abstract: In budding yeast meiosis, the formation of class I interference-sensitive crossovers requires the ZMM proteins. These ZMM proteins are essential in forming a mature synaptonemal complex, and a subset of these (Zip2, Zip3, and Zip4) has been proposed to compose the core of synapsis initiation complexes (SICs). Zip4/Spo22 functions with Zip2 to promote polymerization of Zip1 along chromosomes, making it a crucial SIC component. In higher eukaryotes, synapsis and recombination have often been correlated, but it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
233
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(256 citation statements)
references
References 62 publications
(93 reference statements)
22
233
1
Order By: Relevance
“…The analysis of the two negative controls showed that the error rates for gene conversion identification to be 0-5% (SI Appendix, Table S4), consistent with PCR results in Table 2. Our analysis hence largely confirms the prior higher estimates based on immunolocalization data (14) and suggests that at a minimum 90% of recombination events are resolved as gene conversions.…”
Section: Estimating Lower Bounds For the Number Of Gene Conversion Evsupporting
confidence: 85%
See 1 more Smart Citation
“…The analysis of the two negative controls showed that the error rates for gene conversion identification to be 0-5% (SI Appendix, Table S4), consistent with PCR results in Table 2. Our analysis hence largely confirms the prior higher estimates based on immunolocalization data (14) and suggests that at a minimum 90% of recombination events are resolved as gene conversions.…”
Section: Estimating Lower Bounds For the Number Of Gene Conversion Evsupporting
confidence: 85%
“…This direct estimate, however, disagrees with indirect inferences. An immunolocalization study (14) suggests in excess of 200 recombination events per meiosis, whereas another (15) suggests a more modest 120-140. Assuming that these events mostly reflect non-CO recombination events, this suggests a considerable excess of gene conversion compared with CO.…”
mentioning
confidence: 99%
“…In this study, up to ∼150 AtDMC1 foci were detected in the Col-0 wild type at mid-prophase I. This is somewhat less than the figure reported in a recent study using the Arabidopsis ecotype Ws, where >200 AtDMC1 were recorded (Chelysheva et al 2007). Nevertheless, in both cases the figures are considerably greater than the peak number of AtSPO11-1 foci (∼90) that we observed.…”
Section: The Role Of Atspo11-1 In Programmed Dsb Formationcontrasting
confidence: 77%
“…7). However, in Arabidopsis, the number of MRE11 foci exceeds the expected number of ENs (as estimated by Dmc1 foci, Chelysheva et al 2007), and in tomato, immunogold localization revealed that most of the gold label at all early prophase I stages is associated with AE/LEs, not ENs. Only about 10% of ENs label with gold regardless of whether the preparations are treated with DNase I, prepared using sucrose step gradients, or labeled with ultrasmall gold-conjugated antibodies, all procedures that should increase antibody access to ENs.…”
Section: Discussionmentioning
confidence: 92%